Paul Celans Gedicht "Psalm" und der jüdische Gottesname JHWH - Wiesmüller, Wolfgang (Protokolle zur Bibel, 2005)
The numerous interpretations of Celan’s poem „Psalm“ tend to relativise the blasphemic gestus of the text. In contrast to such tendencies Celan questions the Jewish image of God. His radicality is to be emphasised. Considering Celan’s speech given on the occasion of the Büchner Preis, the application of YHWH, the Hebrew name of God, to the lyrical speaker appears as the „Gegenwort“. The „Gegenwort“ is expressed when facing the emptiness of transcendence. An experience which is caused by the Shoa both biographically and historically. When regarding the context of the lyric prayers written after 1945 Celan either shows possibilities how to write poems after Auschwitz. And furthermore, he even serves justice to a theology of prayer after Auschwitz, which is pleading for a „Hermeneutik des Bruchs“ (Th. Dienberg).